1998
DOI: 10.1007/bf02389313
|View full text |Cite
|
Sign up to set email alerts
|

Solitary plasmacytoma of the calvarium: a review of clinical and prognostic features

Abstract: Primary craniocerebral plasmacytomas are uncommon they represent only 0.7% of all plasmacytomas. We report one case of solitary plasmacytoma of the skull and discuss the clinical features and prognosis of this tumor. There seems to be no difference in prognosis between plasmacytomas originating from the bone (osseous form) and those originating from the dura mater (non-osseous form). In these lesions, the risk of secondary multiple myeloma appears to be low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…[5][6][7][8][9][10][11][12] Intracranial plasmacytomas are associated with cranial nerve palsies and clinical manifestation of space-occupying lesions such as headaches, visual problems, seizures, or paresis. [13][14][15][16][17] As in our case, the patient had headache, left hemiparesis, and seizure.…”
Section: Discussionmentioning
confidence: 95%
“…[5][6][7][8][9][10][11][12] Intracranial plasmacytomas are associated with cranial nerve palsies and clinical manifestation of space-occupying lesions such as headaches, visual problems, seizures, or paresis. [13][14][15][16][17] As in our case, the patient had headache, left hemiparesis, and seizure.…”
Section: Discussionmentioning
confidence: 95%
“…[4] Luigi and Maurizio reported that a right fronto-parietal skull plasmacytoma was found on CT; the patient underwent total removal of the tumor by craniotomy was not followed by any chemotherapy or radiotherapy, and never developed systemic neoplastic disease in 3 years. [5] In contrast, Kyle stated that >80% of patients with an apparently solitary plasmacytoma will eventually develop myeloma. [6]…”
Section: Discussionmentioning
confidence: 99%
“…Patients with solitary skull plasmacytomas often present with several months of slight headaches [5,7] or hearing disturbances, [8] while some patients might have no symptoms at all. Nguyen and Patel noted that a plasmacytoma in one patient was found by her hairdresser.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation